Bimbingan dan perjanjian pranikah sebagai langkah antisipasi disharmoni keluarga - Maulana, Akhmad Ferindra (Maliki Interdisciplinary Journal, 2025)
Marriage is a sacred bond that requires careful preparation. Premarital counseling and prenuptial agreements are crucial in building a harmonious family. Pre-marital guidance acts as a foundation for married life by equipping couples with the necessary knowledge and skills to deal with relationship dynamics. Through guidance, couples can build effective communication, manage conflict well, and have a shared vision of the future of the family. A pre-nuptial agreement serves as a written agreement that regulates the rights and obligations of the couple before marriage. This agreement provides clarity and legal certainty, thus preventing disputes in the future. Thus, both pre-marital counseling and pre-marital agreements are solid foundations in building a harmonious household. Both play an important role in preventing conflict and creating a loving and blessed relationship between husband and wife.